Effect of Silica Xerogel Functionalization on Intensification of Rindera graeca Transgenic Roots Proliferation and Boosting Naphthoquinone Production - Kamil Wierzchowski; Bartosz Nowak; Mateusz Kawka; Katarzyna Sykłowska-Baranek; Maciej Pilarek (Life, 2024)
Secondary metabolites derived from plants are recognized as valuable products with several successful applications in the pharmaceutical, cosmetic, and food industries. The major limitation to the broader implementation of these compounds is their low manufacturing efficiency. Current efforts to overcome unprofitability depend mainly on biotechnological methods, especially through the application of plant in vitro cultures. This concept allows unprecedented bioengineering opportunities for culture system modifications with in situ product removal. The silica-based xerogels can be used as a novel, porous biomaterial characterized by a large surface area and high affinity to lipophilic secondary metabolites produced by plant tissue. This study aimed to investigate the influence of xerogel-based biomaterials functionalized with methyl, hydroxyl, carboxylic, and amine groups on Rindera graeca transgenic root growth and the production of naphthoquinone derivatives. The application of xerogel-based scaffolds functionalized with the methyl group resulted in more than 1.5 times higher biomass proliferation than for reference untreated culture. The naphthoquinone derivatives’ production was noted exclusively in culture systems supplemented with xerogel functionalized with methyl and hydroxyl groups. Applying chemically functionalized xerogels as in situ adsorbents allowed for the enhanced growth and productivity of in vitro cultured R. graeca transgenic roots, facilitating product isolation due to their selective and efficient accumulation.